2015
DOI: 10.1111/jcpp.12398
|View full text |Cite
|
Sign up to set email alerts
|

Practitioner Review: Pathways to care for ADHD – a systematic review of barriers and facilitators

Abstract: BackgroundAttention‐Deficit/Hyperactivity Disorder (ADHD) is a common neurodevelopmental disorder starting in childhood that may persist into adulthood. It can be managed through carefully monitored medication and nonpharmacological interventions. Access to care for children at risk of ADHD varies both within and between countries. A systematic literature review was conducted to investigate the research evidence related to factors which influence children accessing services for ADHD.MethodStudies investigating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
81
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 55 publications
(212 reference statements)
5
81
0
Order By: Relevance
“…Furthermore, to address the question of urgency, research suggests that it would be necessary to train teachers, as well as to educate parents and other relevant family members. This is because studies of pathways to care [6, 13] and major reviews [64] indicate that service access is affected by parents’ and teachers’ knowledge about ADHD and their interpretation of child behaviour, as well as referral requests by parents. An exploration of such approaches would seem warranted for ADHD, i.e., combining training, guideline implementation, checklists, and collaborative care, with wider education for relevant professionals and society.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to address the question of urgency, research suggests that it would be necessary to train teachers, as well as to educate parents and other relevant family members. This is because studies of pathways to care [6, 13] and major reviews [64] indicate that service access is affected by parents’ and teachers’ knowledge about ADHD and their interpretation of child behaviour, as well as referral requests by parents. An exploration of such approaches would seem warranted for ADHD, i.e., combining training, guideline implementation, checklists, and collaborative care, with wider education for relevant professionals and society.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings from a systematic review showed that barriers to accessing care for children with ADHD can operate at the individual, organizational, or societal level 7. In a longitudinal study (N=162), the majority of parents of children who used specialist services reported barriers to accessing services, with the most common barrier being the lack of information about who could help 8.…”
Section: Introductionmentioning
confidence: 98%
“…These symptoms are associated with academic problems such as lower grades, grade repetition and increased school drop-out [2][3][4][5]. Academic improvement is a common treatment target for children with ADHD with stimulant medication being the most commonly prescribed treatment [6]. Stimulants are clinically effective in reducing ADHD symptoms in the short-and medium term [7,8].…”
Section: Introductionmentioning
confidence: 99%